The forced walking test: A novel test for pinpointing the anesthetic-induced transition in consciousness in mouse - Hwang, Eunjin; Kim, Seunghwan; Shin, Hee-Sup; Choi, Jee Hyun (ELSEVIER SCIENCE BV, 2010)
In consciousness or anesthesia studies, pinpointing the precise moment of consciousness or anesthetic transition has been challenging because of the variable lag time between a treatment and its induced response. Here, we describe a novel behavioral method, a forced walking test, which pinpoints the moment of the anesthetic-induced loss of motion (LOM) without handling the animals manually. The mouse is forced to walk on a treadmill, and an anesthetic drug is administered into the peritoneum via a previously secured injection route. The physical activity and the angle of head posture are tracked using a motion sensor preinstalled on the animal's head. The moments of LOM and recovery of motion (ROM) are identified from the physical activity parameters obtained by the sensor. Comparison of our method with the conventional loss-of-righting-reflex assay showed that the time point of LOM was not significantly different between the two methods when examined with two different types of anesthetic agents, propofol and ketamine/xylazine cocktail. In addition, the electrophysiological signals simultaneously acquired in the cortex and the thalamus of the mouse during the forced walking test showed that the brain rhythms induced by ketamine/xylazine anesthesia were generated and terminated in a time-locked manner with respect to LOM and ROM, respectively. In conclusion, the forced walking test allows an objective and precise detection of anesthetic-induced LOM, as well as ROM during awakening from anesthesia, in test animals. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: SPECTRAL EDGE FREQUENCY; EVOKED POTENTIAL INDEX; GENERAL-ANESTHESIA; BISPECTRAL INDEX; PROPOFOL; BRAIN; ELECTROENCEPHALOGRAM; CONNECTIVITY; SEVOFLURANE; MECHANISMS